Innovations in rural and agricultural finance: Rural banking in Africa: The Rabobank approach - van Empel, Gerard (International Food Policy Research Institute, 2010)
Many people in the vast rural areas of Africa lack access to financial services, and most commercial banks are not interested in moving into these areas due to their low income levels, lack of scale economies, and poor infrastructure. Also, few banks actually understand the most common economic activity in rural areas: agriculture.